Effect of the Geriatric Emergency Department Intervention on outcomes of care for residents of aged care facilities: A non‐randomised trial. (26th November 2019) - Marsden, Elizabeth; Taylor, Andrea; Wallis, Marianne; Craswell, Alison; Broadbent, Marc; Barnett, Adrian; Crilly, Julia
Abstract: Objective: As the population of Australia ages, EDs will experience an increasing frequency of presentations of older adults from residential aged care facilities (RACFs). These presentations are often complex and time consuming in the chaotic and potentially hazardous ED environment. The Geriatric Emergency Department Intervention (GEDI) model was developed to optimise the care of frail older adults, especially RACF residents, in the ED. The aim of the present study was to evaluate the effectiveness of the GEDI model on the primary outcomes of disposition (admission, discharge or death) and ED length of stay for residents of RACFs, presenting to an ED in regional Queensland, Australia. Methods: GEDI is a nurse‐led, physician‐championed, innovative model delivered by advanced practice nurses with expertise in gerontology. This quasi‐experimental pragmatic study compared outcomes for RACF residents who presented to a regional Queensland ED during three time periods: pre‐GEDI, interim GEDI and post‐GEDI implementation of the GEDI model. Outcomes included disposition, ED length of stay, ED re‐presentation and mortality. Results: A significant increase in the likelihood of discharge from ED (hazard ratio 1.15, 95% confidence interval 1.05–1.26) and reductions in ED length of stay (hazard ratio 1.49, 95% confidence interval 1.24–1.78) were evident for RACF residents following the implementation of the GEDI intervention. There were no differences in mortality, ED re‐presentation or in‐hospital length of stay between the three time periods. Conclusion: There is a paucity of evidence to support the implementation of nurse‐led teams in EDs designed to target older adults living in RACFs. The GEDI model was effective in reducing ED length of stay while increasing the likelihood of safe discharge for RACF residents.